World Economic and Social Survey 2011 - United Nations Department of Economic; Social Affairs (United Nations, 2011)
This survey explains why the Great Green Technological Transformation will have to be fully realized in developing countries if they are to achieve food security and rural development, minimize the damage from natural hazards and extreme disasters partly induced by climate change, and transform their economies to beat destitution and create productive jobs. Avoiding the climate change tipping point will require fundamental shifts in existing technologies to transform manufacturing, agriculture, living arrangements and infrastructure and thereby reduce greenhouse gas emissions, make more efficient use of natural resources and derivatives, create less waste, preserve biodiversity and reduce social disparities. The survey assesses options and policies to facilitate a new technological revolution, and the challenges societies face in achieving sustainable development and poverty reduction.